2008
DOI: 10.1108/14684520810889682
|View full text |Cite
|
Sign up to set email alerts
|

e‐Government process and incentives for online public financial information

Abstract: Purpose -The aim of this paper is to examine the extent of financial information made available by public administrations on their web sites and to discover whether this communications policy is influenced by the context in which the public entity operates. Design/methodology/approach -The study took as its reference the prior literature and distinguished three dimensions -information content, qualitative characteristics of information and accessibility -which were converted into a disclosure index that was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1
18

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(68 citation statements)
references
References 46 publications
3
40
1
18
Order By: Relevance
“…These findings are reliable to some degree with those reported in studies led in created countries i.e. [9], [10], [11], [22] and [17], in this way demonstrating that variables, which focus the adoption of eGovernment services, identified in created countries could be appropriate in the setting of creating countries. Regardless of the way that the utilization of understudy subjects may have restricted the generalizability of the findings of this study, the research gives helpful experiences into the motivations basic the intentions to utilize e-Government services in creating countries.…”
Section: Literature Reviewsupporting
confidence: 77%
“…These findings are reliable to some degree with those reported in studies led in created countries i.e. [9], [10], [11], [22] and [17], in this way demonstrating that variables, which focus the adoption of eGovernment services, identified in created countries could be appropriate in the setting of creating countries. Regardless of the way that the utilization of understudy subjects may have restricted the generalizability of the findings of this study, the research gives helpful experiences into the motivations basic the intentions to utilize e-Government services in creating countries.…”
Section: Literature Reviewsupporting
confidence: 77%
“…Previous studies oriented to the analysis of the explanatory factors of e-government development present several divergences in relation to the determinants of the level of sophistication of the online presence of public administrations (West, 2000(West, , 2001(West, , 2002(West, , 2003(West, and 2004Laswad et al, 2005;Caba et al, 2005;Torres et al, 2005;Torres et al, 2006;Pina et al, 2007;Pina et al, 2009;Caba et al, 2008;Cárcaba and García, 2008;Gandía and Archidona, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, their prediction was not supported by the results of their studies. Likewise, Pérez, Bolívar and Hernández (2008) found that the Spanish public sector with Internet promotion policies tended to provide more financial-budgetary information. Ojah and Mokoaleli-Mokoteli (2012) also found that, aside from corporate governance structure, physical and institutional infrastructures are important determinants of a country's adoption of the IFR.…”
Section: Internet Penetration and Ifrmentioning
confidence: 96%